The Effect of Combining the Discovery Learning with Problem Based Learning on Students' Problem Solving Ability in Biology Learning - Fransiska Manek; Nugroho Aji Prasetyo; Zuni Mitasari (Universitas Veteran Bangun Nusantara Sukoharjo, 2022)
This study aims to determine the effect of a combination of Discovery Learning and Problem Based Learning on the problem solving abilities of class X students at SMA Negeri 9 Malang. The method used in this research is quasi-experimental with a quantitative approach. Data collection techniques used were interviews, problem-solving ability tests, sheet validation and documentation. The results showed that there was a significant influence on the problem solving abilities of students using a combination of Discovery Learning and Problem Based Learning models in biology class X IPA Malang State High School which can be seen from the sig (2tailed) value of 0.002<0.05. The combination of the Discovery Learning model with Problem Based Learning provides opportunities for students to be actively involved in the learning process to solve problems that occur in everyday life starting from finding problems, analyzing problems to drawing conclusions